Rekonstruksi Paradigma Teologis Dan Pedagogis Literasi Islam Wasathiyah Dalam Konteks Krisis Identitas Keagamaan Generasi Z Di Era Post-Truth - Nabiilah Tsabitul ‘Azmi; Mukh Nursikin (JOURNAL SAINS STUDENT RESEARCH, 2025)
The post-truth era is characterized by the blurring of the boundaries between fact and opinion, as well as the dominance of emotions and subjective perceptions over objective truth. This condition has serious implications for the formation of the religious identity of Generation Z who live in the flow of digital information without adequate epistemic filters. This phenomenon gives rise to a religious identity crisis in the form of the emergence of extreme, shallow, and fragmented religious attitudes. This article aims to reconstruct the theological and pedagogical paradigm of wasathiyah Islamic literacy as a conceptual solution to this problem. Using a qualitative-descriptive approach based on literature review, this study re-examines the theological basis of wasathiyah values, such as justice, balance, and tolerance, and their relevance in contemporary Islamic educational practices. The results of the study indicate that the reconstruction of the wasathiyah Islamic literacy paradigm must be directed at three main aspects: (1) strengthening critical epistemology in understanding religious texts, (2) forming moderate character through reflective and dialogical pedagogy, and (3) religious digital literacy oriented towards verification and information ethics. Through the integration of theological and pedagogical aspects, Islamic education can serve as a space for the formation of an inclusive, rational, and contextual religious identity for Generation Z amidst the challenges of the post-truth era.